Undergraduate nursing students’ perceptions of the effectiveness of clinical teaching behaviours in Malaysia: a cross-sectional, correlational survey - Mohamed Ludin, Salizar; Mohamed, Nik Fathullah (Churchill Livingstone, 2016)

(untitled)
Background: Clinical teachers are a critical determinant of the quality of nursing students’ clinical learning experiences. Understanding students’ perceptions of clinical teachers’ behaviours can provide the basis for recommendations that will help to improve the quality of clinical education in clinical settings by developing better clinical teachers. Objectives: To understand clinical teaching behaviours and their influence on students’ learning from the perspective of undergraduate nursing students. Design: A cross-sectional, correlational survey. Setting: A Nursing Faculty in Kuantan Pahang, Malaysia. Participants: A sample of 120/154 (78%) students from Year 2 – Year 4 were recruited according to set criteria. Methods: A self-administered questionnaire was employed to collect demographic data, and students’ perceptions of clinical teaching behaviours and their impact on learning using the Nursing Clinical Teaching Effectiveness Inventory (NCTEI). Results: Year 3 and 4 students perceived faculty clinical teaching behaviours positively. There was a significant association between clinical behaviours and their influence on students’ clinical learning. Teachers’ competence rated as the most significant influential factor, while teachers’ personality rated as least influential. Conclusion: Participants were able to identify good behaviours influencing their learning. Overall, they perceived their teachers as providing good clinical teaching, resulting in good clinical learning. Novice clinical teachers and nursing students can use this positive association between teaching behaviours and quality of clinical learning as a guide to clinical teaching and learning.